2015
DOI: 10.3390/soc5020339
|View full text |Cite
|
Sign up to set email alerts
|

Peer Attachment and Cyber Aggression Involvement among Chinese, Indian, and Japanese Adolescents

Abstract: Significant advancements have been made in cyber aggression literature, with many studies revealing the consequences associated with adolescents' involvement in these behaviors. Few studies have focused on cyber aggression involvement in China, India, and Japan. The present study examined differences in cyber aggression perpetration and victimization among 1637 adolescents living in China, India, and Japan, while controlling for face-to-face bullying involvement, individualism, and collectivism. Another aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 56 publications
(93 reference statements)
4
32
1
2
Order By: Relevance
“…Cyberbullying perpetration occurs all over the industrialized world (Lobe et al, 2011; Microsoft, 2012; Wright et al, 2015); however, we tested cross‐cultural differences in cyberbullying process using BGCM postulates. Two important findings emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyberbullying perpetration occurs all over the industrialized world (Lobe et al, 2011; Microsoft, 2012; Wright et al, 2015); however, we tested cross‐cultural differences in cyberbullying process using BGCM postulates. Two important findings emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Lobe, Livingstone, Olafsson, and Vodeb (2011) sampled youth in 25 European countries and showed difference in cyberbullying rates across Europe (see also Del Rey et al, 2015). Focusing on Asian culture, Wright et al (2015) showed that Indian adolescents cyberbullied more than their Chinese or Japanese peers. Finally, Yudes‐Gomez, Baridon‐Chauvie, and Gonzalez‐Cabrera (2018) showed that Columbian adolescents cyberbullied less than Uruguayan and Spanish adolescents.…”
Section: Cross‐cultural Differences In Cyberbullyingmentioning
confidence: 99%
“…Cyber nidane is the word for cyberbullying. In one of the few studies conducted on cyber aggression involvement in India, the researchers found that adolescents from India had higher rates of cyber aggression perpetration and cyber victimization than adolescents from China and Japan (Wright et al, 2015). Other research on negative online behaviors in India has focused on cyber gender harassment, a form of cyber harassment involving similar behaviors as cyber aggression, except these behaviors target female adults (Halder & Jaishankar, 2011).…”
Section: Cyber Aggression and Cultural Valuesmentioning
confidence: 97%
“…There is compelling evidence that being a target of bullying victimization is not only linked to negative consequences during childhood and adolescence (reviewed by Wolke & Lereya, 2015), but also results in adverse effects psychologically and physically that last into adulthood (Arseneault, 2018; Baier et al, 2019; Copeland et al, 2013; Moore et al, 2017; Takizawa et al, 2014; Zarate-Garza et al, 2017). Meanwhile, bully/victims display similar or even worse long-term outcomes than those who are solely victims in adulthood (Copeland et al, 2013; Wolke et al, 2015).…”
Section: The Long-term Mental Health Consequences Of Bullying Involvementioning
confidence: 99%
“…The prevalence of bullying victimization in China has been reported to range from 15.8% to 41.6% in primary and 4% to 35.4% in secondary school students; and that of bullies from 5% to 14.1% in primary and 1.5% to 18.4% in secondary school (Hu & Li, 2019; Otake et al, 2019; Zhang et al, 2016). Direct comparisons indicate lower bullying victimization rates in China compared to the USA (Xie et al, 2016), India (cyberbullying, Wright et al, 2015), Japan, Portugal, Spain, and Italy (Eslea et al, 2004). Indirect support also comes from a study on Chinese, Polish, and American students, indicating that the higher the individualism in the culture, the greater the tendency towards direct and indirect aggressive behavior (Forbes et al, 2009).…”
Section: Bullying Involvement In Chinamentioning
confidence: 99%